IMPLEMENTATION OF ARTICULATE STORYLINE LEARNING MEDIA IN CULTIVATING STUDENTS’ CHARACTER IN THE DIGITAL ERA - Fatqurhohman; Hairul Huda (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
Character education is a vital part of student development in the digital era. This study aims to examine the impact of using Articulate Storyline interactive learning media on shaping students’ character, with a focus on honesty, social awareness, and responsibility. A mixed method approach was employed, involving 50 students from SD Muhammadiyah Paleran. Quantitative data were collected via Likert-scale questionnaires distributed through Google Forms, while qualitative data were obtained from in-depth interviews with students representing various character behaviors. Quantitative data were analyzed descriptively, and qualitative data were analyzed using Miles and Huberman’s interactive model. The findings indicate that most students showed improvement in understanding and applying character values ​​through the use of the Articulate Storyline Learning Media. However, some students still require additional support to demonstrate these character traits consistently.